1986
DOI: 10.1177/002199838602000304
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Fracture of Laminates with Holes

Abstract: The methods currently used for predicting static fracture of notched composite laminates in tension, such as the point and average stress criteria and the inherent flaw criterion, are of semi-empirical nature and have limited applicability with respect to size and shape of the notch. In this paper, a damage zone analysis, based on more fundamental concepts, is used to predict fracture of laminates with circular holes of various radii, and oval and rectangular holes of various sizes. The damage is represented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Generally, carbon fibre-reinforced plastics (CFRP) have been the composite material of choice for use in primary structures due to their high specific strength and modulus. As such, a considerable literature exists on the damage characteristics of notched CFRP laminates [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, carbon fibre-reinforced plastics (CFRP) have been the composite material of choice for use in primary structures due to their high specific strength and modulus. As such, a considerable literature exists on the damage characteristics of notched CFRP laminates [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The hat denotes quantities from the reference FEA. The FFM model is compared against a finite element cohesive zone model (CZM), which proved to provide reliable failure load predictions for uniaxially loaded open-hole plates [5]. The model uses a stress based criterion in order to determine …”
Section: Failure Modelsmentioning
confidence: 99%
“…Some researcher conducted experimental tests to further understand the notch failure under tension [10][11][12] as well as under compression [13,14]. A study showed that the load-strain behavior by the hole edge becomes nonlinear at about half the fracture load for carbon/epoxy composites, which suggests that damage initiates at this load level resulting in a more compliant material [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that the load-strain behavior by the hole edge becomes nonlinear at about half the fracture load for carbon/epoxy composites, which suggests that damage initiates at this load level resulting in a more compliant material [10]. Another study found that the correlation drawn between the notch strength and the characteristic length was that the characteristic length decreased as the notched strength increased [12].…”
Section: Introductionmentioning
confidence: 99%